2020
DOI: 10.28982/josam.749996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and short-term outcome of dialysis-requiring acute kidney injury in critically ill patients

Abstract: Ethics Committee Approval: Ethics committee approval was not received due to retrospective design of the study. All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Etik kurul onayı çalışmanın retrospektif dizaynından dolayı alınmamıştır. İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve daha sonra yapılan değişiklikler uyarınca gerçekleştirilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…In a study examining AKI in a cohort of 1689 ICU patients, sepsis was identified as the primary cause of acute kidney injury necessitating dialysis [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining AKI in a cohort of 1689 ICU patients, sepsis was identified as the primary cause of acute kidney injury necessitating dialysis [20].…”
Section: Discussionmentioning
confidence: 99%